Efektifkah Experiential Marketing di Sebuah Rumah Sakit ? - Tiwik Setyawati; Gede Sri Darma (Jurnal Manajemen dan Bisnis, 2018)
ABSTRACT               The success of a business are depends on ideas, opportunities and stakeholders. Businesses must be able to create new ideas in order to provide value to consumers. In addition, business people must be able to see the business opportunities that grow. The actions taken by management must be in reaching opportunities and overcoming challenges to provide customer service in line with experiential marketing. One of the business that is developing at this time is the health business that is the hospital so that researchers choose the hospital as one of the object of research.                The research conducted at Surya Husadha Hospital Nusa Dua has the objective to know, analyze and interpret the effectiveness of experiential marketing implementation. This research is a qualitative descriptive by using phenomenological approach and rationalistic approach. The data process begins by reviewing all the data collected from various sources,  from interviews, observations already written in field records, personal documents, official documents, drawings, photographs, etc., resulting in a broad, general and detailed analysis.               From the research result, it can be concluded that the management of Surya Husadha Nusa Dua has been effective in applying experiential marketing, but there are still things that need to be improved in experiential marketing enforcement that is from the sense dimension need the response of officer to avoid complaints and improvement of service facility; from the Feel dimension purlu an increase in human resource competence; from the Think side of a comfortable layout and providing parking area.